The Banking Stock Market’s Reaction Around the Time of the Finance Minister’s Replacement - Rahardian Resza Fernanda; Suhita Whini Setyahuni; Amalia Nur Chasanah; Pradana Jati Kusuma (Advances: Jurnal Ekonomi & Bisnis, 2026)
Indonesia Stock Exchange to the announcement of the Finance Minister’s replacement. It tests whether daily average abnormal returns (AAR) differ throughout the event window and whether AAR differs between the pre- and post-announcement periods. Research Method: A quantitative event-study design was applied to 45 banking issuers that remained actively traded during an 11-day event window, from t−5 to t+5, producing 495 observations. Abnormal returns were calculated from daily closing stock prices and Composite Stock Price Index returns. Because most data were non-normally distributed, the Friedman Test and Wilcoxon Signed-Rank Test were employed. Results and Discussion: Daily AAR differed significantly across the event window (χ² = 49.341; p = 0.000), with the strongest difference occurring between t−2 and t+2 (p = 0.002). AAR also differed significantly before and after the announcement (Z = −3.883; p = 0.000). The findings indicate that the replacement was interpreted as a relevant political-economic signal and generated a short-term market adjustment. Implications: Investors should incorporate political-economic developments into investment analysis, while policymakers should communicate policy directions consistently to reduce uncertainty. Future studies should include other sectors, longer event windows, and additional market indicators. Originality: This study provides specific evidence on Indonesian banking-stock reactions to a Finance Ministerial replacement using nonparametric event-study analysis.